DIGITAL CONSUMER – HOW TO PROTECT ONE IN BIG DATA ECONOMY - Savanets, Lyudmyla; Stakhyra, Hanna (Актуальні проблеми правознавства, 2021)
Article is devoted to issues of protection digital consumer rights in case of conclusion contracts for the supply digital content. The authors analyze concept and main features of digital consumer, conducts a comparative analysis of it under Ukrainian and European Union law.In the article authors also taking into account main problems which consumer can meet in process of concluding digital content contracts. Above-mentioned problems include: information problems, connected with click-wrap license, browse wrap license, when consumer agree with all provisions, represented by supplier without any possibility to change it. Authors concentrate also on problem with the access to digital content, which includes technical access issue, lock-in and lock-out situation that are the result of product bundling. Taking into account that access issue and luck of information closely connected with unfair terms in contract of the supplying digital content, the authors analyze the most widespread unfair terms, such as reservation to unilaterally change the conditions of contract, exclusion of liability for several types of damage, provision stating that product only works with software or hardware provided by the same vendor or supplier proffered the vendor. Authors point out the problem of protection consumer’s personal data in cases of concluding contracts for the supply digital content in Internet. The borders of using consumer’s personal data, collection and further using it for sell and selection of contextual advertising are researched.In the article, authors pay special attention to the need for novelization of Ukrainian legislation in the field of protection the digital consumer rights, special when it is a tendency for building Big data economy world, and in the light adaptation Ukrainian legislation to aquis communitare European Union.